Influence of Body Mass Index on the Prognostic Value of Tumor ¹⁸F-FDG Uptake in Stage I Non-Small Cell Lung Cancer. - Seung Hyup Hyun; Kyung-Han Lee; Joon Young Choi; Byung-Tae Kim; Jhingook Kim; Jae Ill Zo; Hojoong Kim; O Jung Kwon; Hee Kyung Ahn (PLoS ONE, 2015)
The impact of host energy balance status on outcome of lung cancer has not been fully explored. It is also unknown if there is a potential modifying effect of body mass index (BMI) on tumor cell behavior in patients with early-stage non-small cell lung cancer (NSCLC). We therefore investigated the interactive effects of tumor [18F]-fluorodeoxyglucose (FDG) avidity and BMI.We investigated 1,197 patients with stage I NSCLC who underwent preoperative FDG positron emission tomography followed by curative resection. The primary outcome measure was disease-free survival (DFS). A multivariable Cox proportional hazards model was used to assess the potential independent effects of the prognostic variables. A stratified Cox regression analysis was also performed to assess the potential modifying effects of BMI on the relationship between tumor FDG uptake and patient survival.There were 145 tumor recurrences and 19 deaths during a median follow-up of 30 months. Tumor-related variables, including tumor size, maximum standardized uptake value (SUVmax), histologic cell type, differentiation, lymphovascular invasion, and visceral pleural invasion, did not differ significantly according to BMI status. In multivariable Cox regression analysis, overweight or obesity [hazard ratio (HR), 0.59; 95% CI, 0.43-0.81; P = 0.001] and tumor SUVmax (HR, 1.72; 95% CI, 1.43-2.07; P < 0.001) were significantly associated with DFS. There was a significant modifying effect of BMI (P for interaction < 0.001 in multivariable analysis). High tumor SUVmax was more strongly associated with worse DFS in normal weight patients (HR, 4.72; 95% CI, 2.77-8.06; P < 0.001) than in overweight or obese patients (HR, 2.61; 95% CI, 1.58-4.31; P < 0.001).Tumor FDG avidity is an independent predictor of DFS in patients with early-stage NSCLC and this prognostic value was strengthened in normal weight patients than in overweight or obese patients. These results suggest that the host-tumor interaction between host energy balance status and tumor glucose metabolism plays an important role in the outcome of early-stage NSCLC.